Intellectual Property Rights - Lakshmana Prabu, Sakthivel; Narasimman Kuppusami Suriyaprakasha, Timmadonu (IntechOpen, 2017)
In today's world, we live with the notion that economic health and firm competitiveness are closely tied. Innovation and creativity play a significant role in achieving economic, social, and technological advancement, contributing to a nation's prosperity and leading to job growth for a country. Industries can capitalize on economic benefits through the development and commercialization of innovative products. This also works for consumers, who prefer to purchase safe, guaranteed products, believing that the IP rights of the products are worth protecting both nationally and internationally. The topics covered in this book include an "Introduction to Intellectual Property Rights," "Patenting in the Pharmaceutical Industry," "Towards More Inclusive IP Analysis by Frontier Tools," "Patent Data in Economic Analysis," "How to Elaborate and Interpret an Expert Report on the Design Area," and "Host-Country Patenting and Inventorship in Emerging Countries."